Hemoptysis: A rare presentation of mixed gonadal dysgenesis - Darvin V Das; P K Jabbar; Ramesh Gomez; T P Seena (Wolters Kluwer Medknow Publications, 2020)
The objective of the study was to present a case report on a phenotypic male mixed gonadal dysgenesis (MGD) who presented with hemoptysis due to secondary lung metastasis from dysgerminoma. Phenotypic male MGD (45, X/46, XY) with primary infertility and hemoptysis participated in the study. This study was conducted at a tertiary care center. Laparoscopic visualization of gonads and presence of Müllerian/ Wolffian structures were ascertained. Gonadectomy of intra abdominal dysgenetic gonad were done. Fluorescence in situ hybridization analysis was done in gonadal tissue to find the presence of Y chromosome. Intra-abdominal gonad showed dysgerminoma changes. Müllerian structures in the form of rudimentary uterus and fallopian tubes were seen. Left inguinal gonad showed normal testicular structures. Chemotherapy for secondary lung metastasis contemplated.